Biofiltration, growth and body composition of oyster Crassostrea rhizophorae in effluents from shrimp Litopenaeus vannamei - Azevedo, Rafael; Tonini, William Cristiane; Santos, Marcel José; Braga, Luís Gustavo (Revista Ciência Agronômica, 2014)
The objective of this study was to use oyster as biofilter to improve the quality of effluent from shrimp farming and to assess its growth performance and body composition. It was distributed 1,080 oysters into lanterns in fiberglass tanks (170 L) in a completely randomized design with three treatments (0, 60 and 120 oysters) and six replicates. It was used the effluent from the sedimentation tank. It was measured weekly: temperature, salinity, dissolved oxygen and pH, and it was analyzed ammonia-N, nitrite-N, nitrate-N, orthophosphate-P, suspended solids and chlorophyll-a of the input effluent. The control tanks (without oysters) were more efficient at removing ammonia-N, nitrite-N, nitrate-N and orthophosphate-P. The tanks containing oysters were more efficient at removing suspended solids and chlorophyll-a. Stocking density influenced the height growth of oysters, but not width. Wet and daily weight, condition and yield index were not affected by stocking density, and a significant increase in comparison to the initials values was observed. Body composition was not affected by stocking density, and a significant difference (p0.05). Under the conditions evaluated, the oyster Crassostrea rhizophorae improves water quality and presents growth rates and body composition similar to those obtained in traditional crops.